A new species of Polystemma (Apocynaceae, Asclepiadoideae, Asclepiadeae, Gonolobineae) from the state of Oaxaca, Mexico - Alvarado-Cárdenas, Leonardo O.; García-Mendoza, Abisaí Josué; Sandoval-Gutiérrez, Daniel; Lozada-Pérez, Lucio (Phytotaxa, 2024)
We describe a new species of Polystemma endemic to Oaxaca, Mexico. Polystemma leopardum is similar to P. cordatum but differs in the shape of the corolla lobes, flower color pattern, shape of the gynostegial corona and stylar head, as well as its specialized habitat. We describe and discuss its morphology and provide illustrations and a distribution map. We propose its conservation status as Endangered under the criteria of the IUCN. This discovery increases the diversity of the genus in the country to ten species.